Extractive Spectrophotometric Method for Determination of Acipimox in Capsule - Thangabalan, B.; Vijayaraj Kumar, P. (Asian Journal of Chemistry, 2011)
A sensitive and rapid extractive spectrophotometeric method has been developed for the assay of acipimox in pharmaceutical formulation. The method is based on the formation of a chloroform soluble ion-pair complex between acipimox and methylene blue in a basic medium. The complex shows absorption maximum at 662 nm and the system obeys Beer's law in the concentration range of 2-10 μg/mL. The results obtained by the proposed method were validated statistically and by recovery studies.